Moral Assessment of Violations of Marital Vows Among Christian Couples In Urhoboland - Felix Ogheneochuko Erhabor; Peter O.O. Ottuh (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
The majority of people, especially among the Urhobo, seem to view marriage as their final resort when it comes to getting over issues like loneliness, sexual tension, and social, cultural, economic, and political constraints. However, marriages built on these flimsy foundations frequently end in a string of breakdowns when faced with difficulties, which results in the breaking of marital vows. Due to the above, this work examines the morality of Christian couples in Urhoboland, Delta State, and Nigeria who break their marital vows. The inquiry made use of both analytical and phenomenological approaches. This work was evaluated using a systematic questionnaire and unstructured oral interviews. As a result, 12 churches in six local government areas were selected (Ethiopia East, Ethiopia West, Udu, Ughelli North, Ughelli South, and Sapele Local Government Areas). The phenomenological and analytical procedures were used due to the versatility of survey designs, which allow for a wide range of data collection techniques. The investigation in this work was done under two headings: factors responsible for violations of marriage vows and effects of marriage vow violations on couples, families, and society. This study shows a number of elements that contribute to marital vow breaches as well as the repercussions such violations have on individuals, families, and society. The participants agree that, in general, Christian married couples who divorce have a sense of autonomy and freedom from abusive marriages. This essay contends that since they broke their marital vows, both partners frequently experience severe spiritual regression.